Local wisdom in the Guwosari for its Preservation in the Development of Campus II UIN Sunan Kalijaga - Zamhari, Muhammad; Wirabhuana, Arya; Arief, Syaeful (Universitas Lambung Mangkurat, 2024)
The university's development should not overlook the valuable indigenous knowledge inherited within the local community. Local wisdom comprises the customs and practices that have evolved among particular individuals, rooted in their deep understanding of the local environment accumulated over generations of inhabiting the area. Therefore, when expanding UIN Sunan Kalijaga in the Pajangan region, it is crucial to consider these aspects. This study aims to identify and document the local wisdom present in the Guwosari area, emphasizing its importance for preservation during the development process of Campus II UIN Sunan Kalijaga. A qualitative research method was employed due to the natural setting in which the study was conducted. The findings reveal several enduring legacies of local wisdom, such as the Selarong caves, untouched forests, and the landscapes and waters passed down through the ages. These legacies must be safeguarded and conserved, with development initiatives giving due attention to their protection.